2004
DOI: 10.1007/s00299-004-0810-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transformation of selected mature cork oak (Quercus suber L.) trees

Abstract: A transformation system for selected mature cork oak (Quercus suber L.) trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses were inoculated with A. tumefaciens strains EHA105, LBA4404 or AGL1 harbouring the plasmid pBINUbiGUSint [carrying the neomycin phosphotransferase II (nptII) and beta-glucuronidase (uidA) genes]. The highest transformation efficiency (4%) was obtained when freshly isolated explants were inoculated with A. tumefaciens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 32 publications
0
20
2
3
Order By: Relevance
“…Transformation systems of poplar species (Fillatti et al 1987;Leple et al 1992) have been available for 20 years and the first studies on EM of transformed poplars have been published (Kaldorf et al 2002). With the more recent transformation of larch (Gleeson et al 2005) and birch (Vauramo et al 2006), but also of episodic growing trees like pines (Tang et al 2001) or oak (Alvarez et al 2004), the number of transformable trees is increasing. For the model tree oak, embryogenesis from tissues of mature oak trees (Quercus suber) is possible (Valladares et al 2006;Lopes et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Transformation systems of poplar species (Fillatti et al 1987;Leple et al 1992) have been available for 20 years and the first studies on EM of transformed poplars have been published (Kaldorf et al 2002). With the more recent transformation of larch (Gleeson et al 2005) and birch (Vauramo et al 2006), but also of episodic growing trees like pines (Tang et al 2001) or oak (Alvarez et al 2004), the number of transformable trees is increasing. For the model tree oak, embryogenesis from tissues of mature oak trees (Quercus suber) is possible (Valladares et al 2006;Lopes et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Various studies show that members of the Fagaceae can be transformed using A. tumefaciens by manipulating several factors (Á lvarez et al 2004;Corredoira et al 2004Corredoira et al , 2006Polin et al 2005;Seabra and Pais 1998). In previous experiments (Á lvarez et al 2004), we observed that cork oak somatic embryos were susceptible to AGL1, a disarmed succinamopine-nopaline strain of A. tumefaciens (Lazo et al 1991).…”
Section: Introductionmentioning
confidence: 91%
“…Genetic transformation protocols for cork oak embryogenic lines induced from both mature (Alvarez et al 2004) and juvenile (Sánchez et al 2005) materials through coculture with different strains of Agrobacterium tumefaciens harboring plasmids containing marker genes have been defined. An optimized protocol for Agrobacterium-mediated transformation of mature embryogenic masses of this species, in which variables such as the genotype, explant type, and the preculture period were studied, has also been reported (Alvarez and Ordás 2007).…”
Section: Genetic Transformationmentioning
confidence: 99%